ANALYZING PRESIDENTIAL COMMUNICATION BREAKDOWNS: INSIGHTS INTO TRUMP’S LEADERSHIP APPROACH - Smith, John (Research Journal of Literature, Languages and Linguistics, 2024)
The communication style and shortcomings of the presidency of Donald Trump are examined in this article. The author argues that Trump's communication and leadership style failed as it was based on an authoritarian and autocratic corporate model that did not work in a democratic system. The article examines Trump's lack of critical thinking skills, response to COVID-19, ego and value issues, and other shortcomings. The author concludes that a President of the United States requires certain characteristics, including intellectualism, compassion, critical thinking skills, honesty, and visionary thinking. The article suggests that Trump's presidency was an experiment that failed because he did not possess these qualities. The author further argues that effective communication with the public requires wellthought-out, respectful, and thoughtful dialogue. Finally, the author makes recommendations for future presidents, such as avoiding sound-bite thinking, which reduces complex issues to simplistic statements and avoiding demonizing and blaming past administrations.